Anti-Ulcer Activity of Rhus Coriaria in Indomethacin and Water Immersion Restraint Induced Gastric Ulcer in Experimental Rats (Global Journal of Medical Research, 2015)
The anti-ulcer activity of hydro alcoholic extract of Rhus coriaria Linn (HAERC) was investigated in Indomethacin and Water immersion-induced restraint gastric ulcer in Wistar rats. The assessment was carried out by using ulcer index, ulcer score and histopathological studies of the specimens. HAERC at doses of 145 and 248 mg/kg given orally produced significant inhibition of the gastric lesions induced by Indomethacin and Water Immersion restraint method and the results were comparable to the standard treatment regime. We observed that Rhus coriaria Linn extract exhibits significant anti ulcer activity and thus supports the Unani claims about the drug.
Keywords: rhus coriaria; indomethacin; water immersion induced ulcer model; ulcer index; post sumaq